2017
DOI: 10.5588/ijtld.16.0617
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin skin test and interferon-gamma release assay use among privately insured persons in the United States

Abstract: These results suggest a gradual shift from the use of the TST to the newer IGRAs. Future studies can assess the extent, if any, to which the shift from the use of the TST to IGRAs evolved over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The primary explanatory variable was a categorical variable that detailed the pattern of LTBI testing received within the 6 months prior to isoniazid treatment initiation. Specifically, TST and IGRA testing was identified based on CPT codes, with code 86580 identifying TSTs and codes 86480 and 86481 identifying IGRAs [14]. No otherwise eligible persons had data containing CPT codes 0010T or 86585 so they were not considered in our analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary explanatory variable was a categorical variable that detailed the pattern of LTBI testing received within the 6 months prior to isoniazid treatment initiation. Specifically, TST and IGRA testing was identified based on CPT codes, with code 86580 identifying TSTs and codes 86480 and 86481 identifying IGRAs [14]. No otherwise eligible persons had data containing CPT codes 0010T or 86585 so they were not considered in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the algorithm logic, we required that the data be available to determine if LTBI treatment was completed. We also required that a Current Procedural Terminology (CPT) code for a TST or IGRA [14] be present on a claim within the 6 months prior to treatment initiation, and we required that data describing the individuals' counties of residence be available.…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The information on the unique TB test usage and medical expenditures provides the benchmarks necessary for monitoring private sector testing practices and medical expenditures over time, especially with increased access to private health insurance through the Affordable Health Care Act beginning in 2014. After examining trends in the use of IGRAs and TST among privately insured persons in the United States over a 15-year period (2000–2014), a recent study suggested a gradual shift from the use of TST to IGRAs [ 26 ]. Future studies can examine the trends in the individual test payments, including the associated shift, if any, in the total expenditures from TST to IGRAs over time.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LTBI testing should be targeted toward individuals and populations with known risks [ 25 ]. While it is known that some testing already occurs in the US private sector [ 26 ], it is unknown whether such testing is well-targeted. Understanding the appropriateness of LTBI testing occurring within this increasingly important setting is necessary in order for public health leaders to shape the delivery of these services in the future.…”
Section: Introductionmentioning
confidence: 99%